A clinician's guide to omics resources in dermatology. (1st May 2022) - Doolan, Brent J.; McGrath, John A.; Onoufriadis, Alexandros
Summary: With recent advances in high‐throughput technologies, we are now in an era where the use of large‐scale datasets of biological samples and individual diseases can be analysed using omics methodologies. These include genomics, transcriptomics, proteomics, metabolomics, lipidomics and epigenomics. Omics approaches have been developed to deliver a holistic understanding of systems biology, to identify key biomarkers, and to aid in the interpretation of molecular, biochemical and environmental interactions. Navigating through the plethora of online datasets to find useful and concise information for comparison of data can be complex and overwhelming. The purpose of this article is to review the current repositories and databases, and to evaluate their application in dermatological research and their relevance to clinical practice. For this study, an extensive review of online platforms used in dermatology research was undertaken. Online resources for genetic disease information, genetic disease connection platforms for patients and researchers, clinical interpretation of variants, genome and DNA databases, and omics data repositories and resources were collected. This study provides a comprehensive overview of relevant databases that will aid clinicians and scientists using omics data in dermatology.